Efektivitas Teknik Mind Mapping dalam Layanan Bimbingan Kelompok untuk Meningkatkan Kemampuan Perencanaan Karir Siswa - Rizqi, Salistina Ayu; Putro, Hijrah Eko; Indiati, Indiati (Prosiding University Research Colloquium, 2022)
The purpose of this study was to test the effectiveness of mind mapping techniques in group guidance services to improve the career planning skills of eighth grade students of SMP N 3 Bulu Temanggung. This type of research is a quantitative research with an experimental method of one group pre-test post test design. This research was conducted in eight meetings with 8 students as research subjects. The data analysis technique used parametric analysis and paired sample t-test. The results showed that there was a change in students' career planning before and after participating in group guidance services with mind mapping techniques (Sig. (2-tailed) = 0.00 < 0.05). This shows that the mind mapping technique with group guidance services is effective for improving the career planning skills of eighth grade students of SMP N 3 Bulu Temanggung. For this reason, Bk teachers should use mind mapping techniques in group guidance services to improve students' career planning skills.